Interlinking the Renewable Electricity and Gas Sectors: A Techno-Economic Case Study for Austria - Christoph Sejkora; Johannes Lindorfer; Lisa Kühberger; Thomas Kienberger (Energies, 2021)
Achieving climate neutrality requires a massive transformation of current energy systems. Fossil energy sources must be replaced with renewable ones. Renewable energy sources with reasonable potential such as photovoltaics or wind power provide electricity. However, since chemical energy carriers are essential for various sectors and applications, the need for renewable gases comes more and more into focus. This paper determines the Austrian green hydrogen potential, produced exclusively from electricity surpluses. In combination with assumed sustainable methane production, the resulting renewable gas import demand is identified, based on two fully decarbonised scenarios for the investigated years 2030, 2040 and 2050. While in one scenario energy efficiency is maximised, in the other scenario significant behavioural changes are considered to reduce the total energy consumption. A techno-economic analysis is used to identify the economically reasonable national green hydrogen potential and to calculate the averaged levelised cost of hydrogen (LCOH2) for each scenario and considered year. Furthermore, roll-out curves for the necessary expansion of national electrolysis plants are presented. The results show that in 2050 about 43% of the national gas demand can be produced nationally and economically (34 TWh green hydrogen, 16 TWh sustainable methane). The resulting national hydrogen production costs are comparable to the expected import costs (including transport costs). The most important actions are the quick and extensive expansion of renewables and electrolysis plants both nationally and internationally.